Somatic antigens of tropical liver flukes ameliorate collagen-induced arthritis in wistar rats. - Yasir Akhtar Khan; Sadiq Umar; Syed M A Abidi (PLoS ONE, 2015)
Parasitic helminths polarize immune response of their vertebrate hosts towards anti-inflammatory Th2 type and therefore it is hypothesized that they may suppress the inflammatory conditions in autoimmune disorders. The present study was undertaken to investigate in vivo immunomodulatory and therapeutic potential of somatic antigens (Ag) of liver infecting digenetic trematodes [Fasciola gigantica (Fg) and Gigantocotyle explanatum (Ge)] in collagen-induced arthritic (CIA) Wistar rats. The CIA rats were administered subcutaneously with different doses (50 μg, 100 μg and 150 μg) of somatic antigens of Fg and Ge, daily for 21 days, the time period required to establish infection in natural host (Bubalus bubalis). Thereafter, the control, diseased and treated rats were compared for different parameters viz. hind paw thickness; serum interleukins, IL-4 and IL-10, tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ); expression level of matrix metalloproteinases (MMPs) -2, -9, -13 and nitric oxide (NO) in knee joints and patellar morphology. The CIA rats treated with different antigens, Fg-Ag and Ge-Ag, show significant amelioration of the disease by down regulation of serum TNF-α and IFN-γ (p< 0.05) and upregulation of IL-4 and IL-10 cytokines (p< 0.05); inhibition (p< 0.05) of MMPs (-2,-9,-13) and NO in knee joints and improved patellar morphology with decreased synovial hypertrophy and reduced infiltration of ploymorphonuclear cells. The activity of pro as well as active MMPs (-2 and -9) and active MMP-13 in knee joints of CIA rats was very high compared to the control and treatment groups, suggesting the extent of collagen degradation in CIA rats. Interestingly, the highest dose (150 μg) of Ge-Ag almost wiped out MMP-13 expression. The overall findings suggest that the somatic proteins of Ge-Ag appeared to be therapeutically more effective than Fg-Ag, reflecting interspecific molecular differences which could contribute to the ability of these worms to successfully ameliorate the pathology of CIA.